The widow's strike - Taylor, Brad, 1965- (New York : Penguin, 2014)
When a rogue state plots to unleash a genetically mutated virus, the Taskforce counter terrorism unit under Pike Logan and Jennifer Cahill follows a dangerous trail across Southeast Asia to the United States.
Keywords: Special forces (Military science) -- United States -- Fiction; Special operations (Military science) -- Fiction; Suspense fiction